Oblicz Wartość wyrażenia :

1. -(-1/2)³ + (-0,4)³ : (6/5)² x 45/16
2. -[-(-0,75)² + (5/4)²] - 4 x (-1/2) [do potęgi 4]
3. 130 - [(-6)² x 4/3[trzy do potęgi 2] - 3/8 [3 do potęgi 2] - (-0,5)³] : 30/7

________________________________________________________
1. (-0,25)² : (1/8) : (-2)² - (-1000)[do potęgi 0]
2. [(-0,5)³ + 9/4] : [(-0,25) + (-2)²]
3. -(-5)² x 1/5 [5 do potęgi trzeciej] - (2,3 - 5/2)²
4. -4² - 0,4³ : (-0,64) - (1/2) [do potęgi 0]
5. -2² - (13- 7²) - (-0,1)³ x 10³



1

Odpowiedzi

Najlepsza Odpowiedź!
2010-03-03T10:28:14+01:00
1. -(-1/2)³ + (-0,4)³ : (6/5)² x 45/16
-(-1/8)+(-64/1000):36/25*45/16=
1/8-64/1000*25/36*45/16=
1/8-5/40=
5/40-5/40=0

2. -[-(-0,75)² + (5/4)²] - 4 x (-1/2) ⁴
-[-(-75/100)² + (5/4)²] - 4*(-1/2)⁴=
-[-5625/10000+25/16]-4*1/16=
[225/400-625/400]-1/4=
-400/400-1/4=
-1-1/4=-1i1/4


3. 130 - [(-6)² x 4/3² - 3²/8 - (-5/10)³] : 30/7=
130-[36*4/9-9/8+125/1000]:30/7=
130-[16-9/8+1/8]:30/7=
130-[16-1]:30/7=
130-15*7/30=
130-7/2=
130-3i1/2=126i1/2
________________________________________________________
1. (-0,25)² : (1/8) : (-2)² - (-1000)⁰=
625/10000*8/1*4+1=
625/1250*4+1=
1/2*4+1=
2+1=3


2. [(-0,5)³ + 9/4] : [(-0,25) + (-2)²]=
[-125/1000+9/4]:[-25/100+4]=
[-1/8+18/8]:[-1/4+4]=
17/8:15/4=
17/8*4/15=
17/30


3. -(-5)² x 1/5 ³ - (2,3 - 5/2)²=
-25*1/125-(-1/5)²=
-1/5-1/25=
-5/25-1/25=
-6/25


4. -4² - 0,4³ : (-0,64) - (1/2) ⁰=
16-0,064:(-0,64)-1=
16+0,1-1=
15,1


5. -2² - (13- 7²) - (-0,1)³ x 10³=
4-(13-49)-(-1/1000)*1000=
4+36+1=
41